Efficiency Analysis of Sharia Regional Development Banks in Indonesia Using Two-Stages Data Envelopment Analysis - Aliyah, Hikmatul; Maulani, Denia; Marlina, asti (Moneter: Jurnal Keuangan dan Perbankan, 2023)
The main objective of this study is to evaluate the efficiency level of Sharia Regional Development Banks between 2014 and 2017 using the Data Envelopment Analysis (DEA) method. The efficiency analysis results indicate that the efficiency level of Sharia Regional Development Banks during the study period from 2014 to 2017 was quite fluctuating. In 2014, five Sharia Regional Development Banks showed inefficiency, namely Bank DIY Syariah, Bank Jateng Syariah, Bank Jatim Syariah, Bank Kalsel Syariah, and Bank NTB Syariah. In 2015, four Sharia Regional Development Banks showed inefficiency, namely Bank Jateng Syariah, Bank Jatim Syariah, Bank Kaltimtara Syariah, and Bank NTB Syariah. In 2016, five Sharia Regional Development Banks showed inefficiency, namely Bank Jateng Syariah, Bank Sulselbar Syariah, Bank Kaltimtara Syariah, Bank NTB Syariah, and Bank Jatim Syariah. However, in 2017, only two Sharia Regional Development Banks showed inefficiency, namely Bank Jatim Syariah and Bank Kaltimtara Syariah.